2002
DOI: 10.1074/jbc.m201299200
|View full text |Cite
|
Sign up to set email alerts
|

The Stress-activated Protein Kinases p38α and JNK1 Stabilize p21Cip1 by Phosphorylation

Abstract: Stress signals activate the SAPK/JNK and p38 MAPK classes of protein kinases, which mediate cellular responses, including steps in apoptosis and the maturation of some cell types. We now show that stress signals initiated by transforming growth factor-␤1 (TGF-␤1) induce G 1 arrest through protein stabilization of the CDK inhibitor p21Cip1 . TGF-␤1 was previously shown to increase p21 protein levels, which in turn mediated G 1 arrest through inactivation of the CDK2-cyclin E complex in HD3 cells (Yan, Z., Kim, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
202
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(213 citation statements)
references
References 41 publications
(46 reference statements)
7
202
2
2
Order By: Relevance
“…Initial in vitro experiments suggested that Mirk phosphorylated cyclin D1 at Thr 184 , Thr 288 , or both residues (data not shown). However, the activity of kinases can be very different in vitro and in vivo (21), so these experiments were taken only as guides for subsequent studies.…”
Section: Resultsmentioning
confidence: 99%
“…Initial in vitro experiments suggested that Mirk phosphorylated cyclin D1 at Thr 184 , Thr 288 , or both residues (data not shown). However, the activity of kinases can be very different in vitro and in vivo (21), so these experiments were taken only as guides for subsequent studies.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, Raf/MEK/ ERK and MKK3/6-p38 represent two independent mitogen-activated protein kinase (MAPK) pathways. Whereas the Raf/MEK/ERK cascade transduces proliferative signals, the MKK3/6-p38 cascade is a major mediator of stress responses that usually leads to growth arrest or apoptosis (Kim et al, 2002;Xiu et al, 2003;Bulavin and Fornace, 2004;Yee et al, 2004). It was reported that the MKK3/6-p38 cascade functions as downstream of the Raf/MEK/ERK cascade to mediate senescence.…”
Section: Introductionmentioning
confidence: 99%
“…These features of SIPS can result from activation of the stress-associated p38a MAP kinase as the use of the p38 selective inhibitor SB203580 prevents ras-induced senescence in human BJ fibroblasts (Deng et al 2004;Wang et al 2002). Activation of p38 leads to the stabilisation of the cyclin-dependent kinase inhibitor p21 WAF1 and subsequent cell cycle arrest, and also leads to the phosphorylation of the small heat shock protein HSP27 resulting in stress fibre formation (Deng et al 2004;Haq et al 2002;Kim et al 2002).…”
Section: Introductionmentioning
confidence: 99%